Removal of cadmium (II) by graphene oxide-chitosan adsorbent from aqueous solution - Azizkhani, Sepehr; Mahmoudi, Ebrahim; Abdullah, Norhafizah; Ismail, Mohd Halim Shah; Mohammad, Abdul Wahab; Hussain, Siti Aslina (Engg Journals Publications, 2018)
Pollution has a negative influence on the environment and is necessary to eliminate from wastewater and aqueous solution. There are several adsorbents for removing the pollution, among them Graphene oxide and Chitosan are proper elements with great uptaking ability. In this investigation, graphene oxide surface was coated with chitosan paricles to remove the Cadmium (II) from aqueous solution. The impact of concentration, pH and time were studied to achieve the optimum conditions of adsorption. The adsorbent was analyzed by TEM, FT-IR, XRD, and SEM analysis. The outcomes presented that the adsorbent was prepared successfully. The concentration item was tested from 10 to 120 ppm. The pH and time items were studied from 3 to 8 value and from 5 to 140 minutes for eliminating cadmium (II) respectively. Freundlich and Langmuir's models was used and the pseudo-second-order was the best fitted kinetic model in this investigation. Conclusively, the maximum adsorption ability of the made adsorbent was achieved at 107.8 mg/g based on Langmuir isotherm.